Sequências textuais descritivas em cartas de reclamação - Rocha, Débora Ferreira da (2015)
This dissertation is based in the research line of Text and speech in oral and written forms and its theme is the descriptive textual sequences in complaint letters. The general objective of this study is to contribute to a better understanding of descriptive textual sequences present in the genre complaint letters texts. The specific objectives are to identify and analyze the descriptive sequences in complaint letters and interpret their occurrence in this textual genre.In order to develop our study, we have chosen as the theoretical linguistics Textual, to deal with textual typology (TRAVAGLIA, 1991, 2002, 2004a, 2004b, 2007a, 2007b, 2007c, 2009 and 2014), descriptive genre (Marquesi, 2004) textual sequences (ADAM, 2008) and descriptive textual sequences (ADAM, 2008; Marquesi, 2011) and the theory of genres (Bakhtin, 2006 [1979]; Marcuschi (2008), to deal with the genre letter of complaint (GREGÓRIO and Cecilio 2006; MIRANDA, 2004; SILVA and LEAL, 2003; Wilson, 2001; MELO, 1999. The methodology was a review of the literature about text types and descriptive text, textual sequences and descriptive textual sequences, besides the theory that treats textual genre, with special focus on the complaint letter; establishment of categories of analysis, due to the recurrent strategies observed in the selected corpus, newspaper letters selection from the newspaper Diário de S. Paulo and analysis of the corpus according to the categories proposed in the theoretical foundation chapter. The corpus has about 22 complaint letters selected from April to July 2014, in the section A Vez e a Voz do Leitor , from the newspaper Diário de S. Paulo. The results show that the descriptive textual sequences not only indicate as well, along with other textual sequences, contribute in building the argue that the text producer has in mind